An evaluation of the burden placed on the General Internal Medicine team at the Role 3 Hospital in Camp Bastion by UK Armed Forces personnel presenting with symptoms resulting from previously identified disease. Issue 1 (20th February 2015) - Cox, Andrew T; D Linton, T; Bailey, K; Stacey, M; Sharma, S; Thomas, L; Wilson, D
Abstract : Introduction: During previous deployments of the British Armed Forces, a significant proportion of aeromedical evacuations were accounted for with recurrent symptoms from a known disease that had often triggered occupational medical downgrading. Many servicemen and women had deployed inappropriately, and by doing so became a burden on the deployed medical facilities. Commanders performing systematic medical risk assessments prior to departure might have prevented these individuals from deploying. This study was designed to assess the avoidable burden from recurrent disease during the current Afghanistan operation. Methods: A cross-sectional study reviewing the hospital and computerised primary care medical records of consecutive patients admitted under the General Physicians to the Role 3 Hospital in Camp Bastion over 9 months from April 2011. The occupational medical grading, diagnosis, disposal and whether the disease was recurrent were recorded. Results: Of 270 patients admitted, 14 (5.2%) were medically downgraded. The computerised records were unavailable for 31 (11.5%) patients. All those patients who were medically downgraded were graded 'Medically Limited Deployable'. In the downgraded group, only one patient presented with recurrent symptoms from their pre-existing condition (Crohn's disease). In the non-downgraded group, two patients presented with symptoms relating to their previous diagnoses. One presented with a second heat illness and should have been medically downgraded and not have been deployed, while the other patient had previously been investigated for recurrent syncope and was upgraded 6 months prior to deploying. All three patients underwent aeromedical evacuation but only two of these were considered to have been avoidable. Discussion: The number of general medical admissions to the Role 3 Hospital due to a pre-existing disease is very low.